Rancang Bangun dan Penerapan Mesin Ayakan Gula Semut di Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta - Mochamad Syamsiro; Nurwiyanta Nurwiyanta; Erni Umi Hasanah; Muhammad Luk Marsakti; Al Muafi Sandono (Jurnal Mekanika dan Sistem Termal, 2017)
Gula Semut is a sugar made from palm nectar or also called Neera that has gone through several processes before it is ready in a form that convenience for us to consume. This study aims to design and fabricate the vibrating sieve machine to separate gula semut (cristalized sugar) based on particle size. The machine has a capacity of 50 kg/h depending on the raw material. The machine consists of several main parts such as siever, electric motor, vibrating spring, balancer and frame. Simple calculation has been conducted to meet the capacity of the machine. The machine was made of food grade stainless steel to prevent contamination in gula semut due to corrosion. A preliminary experiment has been carried out to evaluate the performance of the machine including adjusting the balancer position. Finally, the machine will increase the productivity of gula semut industry in Kulonprogo District.